Roadie [videorecording (DVD)] - Cuesta, Michael, 1963-; Eldard, Ron, 1964-; Cannavale, Bobby; Hennessy, Jill, 1968-; Smith, Lois, 1930- (Magnolia Home Entertainment, 2012)
Jimmy, a longtime roadie for the legendary Blue Oyster Cult, has been fired by the band. With nowhere else to go, he returns home to see his aging mom in Forest Hills, Queens, where a wild encounter with two old high school friends shows him that some things never change.